Structural characterization and bioactivities of a glucomannan-based polysaccharide (AGP-1) from Arundina graminifolia - Tianhao Dong; Huijuan Wang; Xuemei Lin; Wenzhong Zhao; Kunfa Yang; Fengxi Yang; Genfa Zhu; Jie Gao; Meifeng Liu (Carbohydrate Polymer Technologies and Applications)
This work aims to explore and characterize the functional polysaccharide of Arundina graminifolia. The extraction process of the crude Arundina graminifolia polysaccharides (AGP) was optimized using response surface methodology (RSM). The maximum yield of AGP reached 10.2 % under the optimal conditions of extracting 84.7 min at 96.0 °C, and liquid-material ratio of 27.5 mL/g. Meanwhile, AGP-1, the purified polysaccharide, was obtained using DEAE-Cellulose52 and Sephadex G-200 chromatography, and its structure was analyzed and confirmed by multiple chromatographic and spectroscopic techniques. It was indicated that AGP-1 (Mw 494.3 kDa) was a glucomannan-based polysaccharide mainly consisted of mannose, glucose and galactose at a molar ratio of 10:7:1, and its structure skeleton contained glycosyl residues of Glcp-(1→, →4)-Manp-(1→, →4)-Glcp-(1→, →3,4)-Galp-(1→ and →4,6)-Galp-(1→. Distinct from the β-1,4 glycosidic linkage bonds of other glucomannans, AGP-1 was infrequently linked by α-1,4 glycosidic bonds between monosaccharides of mannose and glucose with a specific molar ratio of 3:2. Furthermore, it was found that AGP-1 exhibited strong DPPH, ABTS, and hydroxyl radicals scavenging abilities, along with excellent inhibition of α-glucosidase activity in vitro. Our finding indicated that AGP-1 possessed a potential as natural antioxidant and hypoglycemic product.